PERDEBATAN PENGGUNAAN HERMENEUTIKA SEBAGAI METODE PENAFSIRAN AL-QUR'AN - MASRUKHIN MUHSIN (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
The word hermeneutics derives from the Greek verb, hermeneuin. It means to interpret and to translate. Hermeneutics is divided into three kinds: the theory of hermeneutics, the philosophy hermeneutics, and the critical hermenmtics. Hasan Hanfi is known as the first scholar who introduces hermeneutics in the Islamic World through his work dealing with the new method of interpretation. Nashr Hamid Abu-Zaid is another figure who has much studied hermenmtics in the classical interpretation. Ali Harb is a figure who also much involved in discussing the critism of text even though he does not fully concern on literature or art, but on the thoughts. Muslim thinker who has similar view with Ali Harab in seeing that the backwardness of Arab-Islam from the West is caused by the system of thoguht used by Arah-Muslim not able to come out of obstinary and taqlid is Muhammad Syahmr. On the other side, ones who refuse hermeneutics argue that since its heginning, hermeneutics must be studied suspiciously because it is not derived from the Islamic tradition, but from the unbeliever scientific tradition, Jews and Chrtians in which they use it as a method to interpret the Bible. Practically, in interpreting the Qur'an, hermeneutics even strengthens something, namely the hegemony of scularism-liberalism in the Muslim World that Muslims must actually destroy. Keywords: Hermeneutics, Tafsir, al qur'an